Management of acute low back pain in emergency departments in São Paulo, Brazil: a descriptive, cross-sectional analysis of baseline data from a prospective cohort study. Issue 4 (1st April 2022) - Oliveira, Indiara Soares; Tomazoni, Shaiane Silva; Vanin, Adriane Aver; Araujo, Amanda Costa; de Medeiros, Flávia Cordeiro; Oshima, Renan Kendy Ananias; Costa, Leonardo Oliveira Pena; Costa, Lucíola da Cunha Menezes
Abstract : Objective: To describe management strategies used in public emergency departments in a middle-income country for patients with acute non-specific low back pain. Design: A descriptive, cross-sectional analysis of baseline data from a prospective cohort study. Setting and participants: A study with 600 patients with low back pain presenting in four public emergency departments from São Paulo, Brazil was conducted. Outcome measures: Diagnostic tests, pharmacological interventions, and/or referral to other healthcare professionals were collected. Descriptive analyses were used to report all outcomes. Results: Of all patients, 12.5% (n=75) underwent some diagnostic imaging tests. Medication was administered to 94.7% (n=568) of patients. The most common medications were non-steroidal anti-inflammatory drugs (71.3%; n=428), opioids (29%; n=174) and corticosteroids (22.5%; n=135). Only 7.5% (n=45) of patients were referred to another type of care. Conclusion: There is a need for research data on low back pain from middle-income countries. There was an acceptable rate of prescription for diagnostic imaging tests. However, there were high medication prescriptions and small rates of referrals to other healthcare services. Our findings indicate that there is still a need to implement best practices in the management of acute low back pain at public emergency departments in Brazil.